Interspecific and intraspecific competitive interactions in Brook charr, Salvelinus fontinalis, and Brown trout, Salmo trutta - Malmros, Andreas (2006)
A large-scale field enclosure experiment was conducted to examine the contradicting information about the competitive interactions between YOY brown trout and YOY brook charr. Interactions that is supposed to be based on aggression and growth capacity. Different densities of brown trout and brook charr were held together and alone in earth ponds for six weeks to evaluate choice of diet and growth rate. There were large differences between brown trout and brook charr in the their growth responses due to intra- and interspecific competition. Brook charr had the highest growth capacity of the two species. Despite that brook charr had a higher growth capacity and also a larger gap than brown trout, had brook charr only higher growth rate than brown trout when alone while brown trout not were affected by the presence of brook charr. Brown trout were less affected by interspecific competition from brook charr and were more affected by intraspecific competition. Since trout had a higher growth rate than charr in the sympatric treatments, this suggests that trout is the better competitor in environments like lakes, ponds and pools where resources are harder to monopolise through interference interactions.